PENGARUH STRATEGIC EXPERIENTIAL MODULES (SEM’s) DAN EMOTIONAL BRANDING TERHADAP BRAND LOYALTY CITRA HAND & BODY LOTION PADA MAHASISWI FAKULTAS EKONOMI UNIVERSITAS JEMBER - Indraningrat, Ketut (BISMA: Jurnal Bisnis dan Manajemen, 2015)
Abstract: The purpose of this study is to analyze the effect of sense, feel, think, act, relate, that is usually called as Strategic Experiential Modules (SEM’s), and emotional branding on brand loyalty Citra Hand & Body Lotion. The sample consists of 70 students of the Faculty of Economics Universitas Jember. The research used multiple regression analysis to test the hypothesis. Results show that there are positive effect of sense, think, act, relate and emotional branding on brand loyalty. But, there is negative effect of feel on brand loyalty. Keywords: Sense, Feel, Think, Act, Relate, Emotional Branding, and Multiple Regression.